Smallholder Farmers’ Coping Strategies to Perceived Climate Change and Variability in Isingiro District, South Western Uganda - Aturihaihi, Christine; Opio, Fina; Tumwesigye, Wycliffe; Beyihayo, Geoffrey Akiiki (East African Nature and Science Organization, 2023)
Climate change and variability pose a major challenge facing the agricultural sector around the world and trends are feared to intensify by 2050. This is likely to complicate agricultural decisions affecting local communities who depend on the sector for their livelihood. Seasonal changes in weather patterns are projected to reduce food production due to the reduction in average yields of common food crops. With the majority of smallholder farmers in Uganda depending on agriculture for survival, building their adaptive capacity to climate change is vital to ensure household food and income security. This study aimed at establishing the smallholder farmers’ perceptions of climate change and their initiatives to cope with and manage the associated risks. A sample of 126 farming households were randomly selected from three Sub counties in Isingiro District and studied using field observations and questionnaires. Key informant interviews were also conducted with three extension workers. The collected data was analysed using Stata 14 and Excel. The findings revealed that there was increasing awareness of the climate change and variability challenge among smallholder farmers with the increasing need to take on adaptation strategies. The results showed that the major perceived changes were, increased intensity and frequency of droughts (98%), increase in daytime temperatures (92.7%), decrease in rainfall intensity (92.1%) and changes in rainfall distribution patterns (90%). It also showed that different initiatives had been taken by farmers to cope with the changes like changing planting dates (92.1%), growing crop variety mixtures (73.8%) and practising soil and water conservation (62.7%). Based on the findings of this study, smallholder farmers greatly perceived climate change and variability with negative impacts imposed on their farming operations. Although farmers have tried to adapt, there is still a need to support their coping strategies through appropriate policies. This will facilitate increased adoption of adaptation measures, thereby reducing the negative consequences of climate change in future